HUMAN RIGHTS AND TOBACCO PRODUCTS: OBLIGATIONS OF STATES UNDER INTERNATIONAL LAW AND PRACTICE IN UZBEKISTAN - Munisa Rayimova Nozim kizi (Modern American Journals, 2025)
This article analyzes the international obligations of states to regulate the circulation of tobacco products and their impact on ensuring the right to health in Uzbekistan's practice. The requirements and standards of the International Covenant on Economic, Social and Cultural Rights and the World Health Organization Framework Convention on Tobacco Control regarding tobacco control are considered as the legal basis. Uzbekistan's legislation and policy measures are compared with these international norms, and the effectiveness of mechanisms aimed at protecting youth health is analyzed. According to the research results, although national policy includes important preventive and control measures, there is a need to improve restrictions on advertising and marketing, regulation of new nicotine products, and strengthening of the monitoring system. In conclusion, it is argued that full compliance with international obligations serves to ensure Uzbekistan's real implementation of the right to health.
Keywords: Tobacco control, right to health, international obligations, WHO FCTC, youth rights, Uzbekistan legislation, preventive policy.